Synthesis of 3-oxo-3-phenyl-2,2,5-trimethyl-1,3-oxaphosphorinanes and their tetrafluoroborate salts - López Cortina, Susana; Elizondo Martínez, Perla; Pérez Rodríguez, Nancy; Hernández Fernández, Eugenio; Fernández Zertuche, Mario (Universidad Autónoma de Nuevo León, 2011)
The synthesis and characterization of cis- and trans-3-oxo-3-phenyl-2,2,5-trimethyl-1,3-oxaphosphorinanes (7a and 7b) and their corresponding tetrafluoroborate salts (3a and 3b), heterocyclic organophosphorus compounds not previously reported in the literature, was accomplished. They were fully characterized by H, C and P NMR. It was established the relative configuration of these compounds on the basis of an X-ray diffraction study of oxide 7a.